If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + -6x = 8 + -10x Solving 24 + -6x = 8 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 24 + -6x + 10x = 8 + -10x + 10x Combine like terms: -6x + 10x = 4x 24 + 4x = 8 + -10x + 10x Combine like terms: -10x + 10x = 0 24 + 4x = 8 + 0 24 + 4x = 8 Add '-24' to each side of the equation. 24 + -24 + 4x = 8 + -24 Combine like terms: 24 + -24 = 0 0 + 4x = 8 + -24 4x = 8 + -24 Combine like terms: 8 + -24 = -16 4x = -16 Divide each side by '4'. x = -4 Simplifying x = -4
| 7t(t-4)-2t(8t-4t+3)=0 | | 7x+39= | | 8x^2-49=0 | | 8x^2+4xy=0 | | 8x=3x+20whatisx | | 7x-14=9x+5 | | 8+6x=-12+x | | 3x-9=x+1whatisx | | 3(5x-2)= | | x^2-9x-27=0 | | 0x-3= | | 6i-20i= | | 8x-5=2x+17 | | 2n^2+10=78 | | 5(2x+6)=-4(-5-6x)+3x | | 6x^2+3x^3=9x+6 | | 5(3p-2)= | | log[5](3x-5)=2 | | 4n^2+8=45 | | -5(7x-2)=-2(3+6x) | | Ln(x^2-9x+5)=0 | | -2=2x+7-3x | | 7(y+3)=42 | | -2+2/3x=10 | | 17+b-4b=-4 | | 2x-x+5=4 | | lnx^6-12=0 | | (5x-1)+(2x+3)=14 | | 1.5x+6x-15=4x+5 | | 5x+8-4x=13 | | 5x^2+6x+72=0 | | 2x+6=-4x-6 |